1996
DOI: 10.1148/radiology.201.2.8888242
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: validation of spiral CT angiography in 149 patients.

Abstract: Spiral CT angiography is an accurate method for the detection and exclusion of PE, with the exception of isolated subsegmental PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0
9

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(140 citation statements)
references
References 0 publications
6
125
0
9
Order By: Relevance
“…With regard to the diagnosis of isolated subsegmental PE, we diagnosed a single case in a group-1 patient with underlying COPD (one of 24 patients with positive angiograms, i.e., 4%). Apart from Goodman et al who identified four cases among 11 positive scans (36%) [2], the reported prevalence of subsegmental PE on single-slice and dual-section spiral CT angiograms varies from 2 to 10% [3,4,6,15].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…With regard to the diagnosis of isolated subsegmental PE, we diagnosed a single case in a group-1 patient with underlying COPD (one of 24 patients with positive angiograms, i.e., 4%). Apart from Goodman et al who identified four cases among 11 positive scans (36%) [2], the reported prevalence of subsegmental PE on single-slice and dual-section spiral CT angiograms varies from 2 to 10% [3,4,6,15].…”
Section: Discussionmentioning
confidence: 96%
“…Compared with single-slice CT, and for a similar degree of functional impairment, we observed a significantly higher proportion of CT angiograms devoid of respiratory (64 vs 38%) and cardiac motion artifacts (62 vs 40%) with multislice CT. Because of the well-known difficulties in assessing acute PE in patients with underlying respiratory disease, the benefit of multislice CT, which allows obtainment of a higher number of examinations interpretable down to the subsegmental pulmonary arterial bed compared with single slice CT, is emphasized. As underlined by several investigators [2,4,14,15], the limitations of single-slice CT in the detection of clots in small vessels are related mainly to lower spatial resolution and to the fact that subsegmental vessels of the upper and lower lobes frequently lie outside the limits of z-axis coverage. Consequently, the remaining indications of pulmonary angiography, namely the exclusion of subsegmental PE after a negative CT angiogram down to the segmental level, are expected to dramatically decline with the widespread availability of multislice CT scanners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Most scans are interpreted as either positive or negative for pulmonary embolism, providing clinicians with a greater sense of diagnostic certainty than with the probabilistic results of lung scintigraphy. Initial studies of CTPA supported this appearance of diagnostic certainty, reporting sen-sitivity and specificity of greater than 90%, 3,4 but several subsequent studies have failed to reproduce these results. [5][6][7] Newer multidetector CT scans are believed to be more accurate than earlier singledetector CT, 8 but true estimates of CTPA test characteristics will not be known until publication of the forthcoming PIOPED II study.…”
Section: S Piral Computed Tomographic Pulmonary Angiography (Ctpa)mentioning
confidence: 98%
“…Several studies have shown a high sensitivity and specificity for spiral CT in the diagnosis of PE [37][38][39]. In an increasing number of centres, spiral CT has become the imaging modality of choice in the diagnosis of PE.…”
Section: Spiral Computed Tomographymentioning
confidence: 99%